Study of Cardiovascular Outcomes in Renal Transplantation: A Prospective, Multicenter Study to Determine the Incidence of Cardiovascular Events in Renal Transplant Recipients in Ontario, Canada. Issue 1 (13th June 2017) - Ribic, Christine M.; Holland, David; Howell, John; Jevnikar, Anthony; Kim, S. Joseph; Knoll, Greg; Lee, Brenda; Zaltzman, Jeffrey; Gangji, Azim S.
Background: Renal transplant recipients (RTRs) are at significantly higher risk for morbidity and mortality compared with the general population, largely attributed to cardiovascular disease (CVD). Previous estimates of CVD events have come from health care databases and retrospective studies. Objective: The objective of this study was to prospectively determine the prevalence of risk factors and incidence of CVD events in a Canadian cohort of RTRs. Design: Study of Cardiovascular Outcomes in Renal Transplantation (SCORe) was a prospective, longitudinal, multicenter observational study. Setting: Adult RTRs were recruited from 6 participating transplant sites in Ontario, Canada. Patients: Eligible patients were those receiving a living or deceased donor renal transplant. Patients who received simultaneous transplant of any other organ were excluded. Measurements: Primary outcomes included myocardial infarction (MI) defined by American College of Cardiology (ACC-MI) criteria, and major adverse cardiac events (MACE), defined as cardiovascular (CV) death, ACC-MI, coronary revascularization, and nonhemorrhagic stroke. CV events were adjudicated by a single, independent cardiologist. Methods: CV and transplant-specific risk factors that predict MACE and ACC-MI were identified by stepwise regression analysis using the Cox proportional hazards model. Results: A total of 1303 patients enrolled across 6 transplant centers were followed for 4.5 ± 1.6 years (mean ± SD). Incidence of MACE was 7.0%, with significant independent predictors/risk factors including age, diabetes, coronary revascularization, nonhemorrhagic stroke, and renal replacement therapy (RRT). ACC-MI incidence was 4.0%, with significant independent predictors/risk factors including age, coronary revascularization, and duration of RRT in excess of the median value (2.91 years). Limitations: Patients were recruited from a single province, so may not reflect the experience of RTRs in other areas of Canada. Conclusions: Using a prospective design and rigorous methodology, this study found that the incidence of CV events after renal transplantation was elevated relative to the general Canadian population and was comparable with that reported in patient registries, thus helping validate the utility of retrospective analysis in this field. SCORe highlights the importance of monitoring RTRs for traditional cardiac and transplant-specific CV risk factors to help prevent CV morbidity and mortality. Further research is needed to investigate a broader range of potential risk factors and their combined effects on incident CV events.